Bottle aging and storage of wines: a review - Echave Álvarez, Javier (2018)
Wine is perhaps the most ancient and popular alcoholic beverage worldwide. Winemaking practices involve careful vineyard management alongside controlled alcoholic fermentation and potential aging of the wine in barrels. Afterwards, the wine is placed in bottles and stored or distributed in retail. Yet, it is considered that wine achieves its optimum properties after a certain storage time in the bottle. The main outcome of bottle storage is a decrease of astringency and bitterness, improvement of aroma and a lighter and more stable color. This is due to a series of complex chemical changes of its components revolving around the minimized and controlled passage of oxygen into the bottle. For this matter, antioxidants like sulfur oxide are added to avoid excessive oxidation and consequent degradation of the wine. In the same sense, bottles must be closed with appropriate stoppers and stored in adequate, stable conditions, as the wine may develop unappealing color, aromas and flavors otherwise. In this review, features of bottle aging, relevance of stoppers, involved chemical reactions and storage conditions affecting wine quality will be addressed.